Afebrile benign convulsions with or without a reversible splenial lesion in two pediatric patients with COVID-19 - Yun Young Lee; Young Ok Kim (BMC Pediatrics, 2023)
Abstract Background Seizures in children with coronavirus disease 2019 (COVID-19) were markedly increased during the Omicron variant surge. Most seizures occurred with fever. New-onset afebrile seizures were rarely reported; therefore, their courses are not well-known. Case presentation Two patients (7 and 26 months of age, respectively) with COVID-19 showed recurrent afebrile seizures immediately after resolution of a fever lasting for 2–3 days. Bilateral convulsive seizures lasted for approximately 1 min/episode (6 of 7 total episodes) and occurred 3–4 times within 2–3 h. However, the patients were alert between seizures, which is in contrast to seizures occurring with encephalopathy or encephalitis. Only one episode required acute antiseizure medication. Brain magnetic resonance imaging showed a reversible splenial lesion in one patient. The serum uric acid level was slightly increased (7.8 mg/dL) in this patient. Electroencephalography findings were all normal. During the follow-up period, no seizures or developmental problems have been observed. Conclusions COVID-19-associated, afebrile benign convulsions with or without a reversible splenial lesion are similar to ‘benign convulsions with mild gastroenteritis’; therefore, continuation of antiseizure medication does not seem necessary.